Acute Vertigo After COVID-19 Vaccination: Case Series and Literature Review - Di Mauro, Paola; La Mantia, Ignazio; Cocuzza, Salvatore; Sciancalepore, Pasqua Irene; Rasà, Deborak; Maniaci, Antonino; Ferlito, Salvatore; Tundo, Isabella; Anzivino, Roberta (Frontiers in Medicine, 2022)
Objective: The aim is to present some cases of acute vertigo potentially related to the Covid-19 vaccine and review the available literature about cochleovestibular dysfunction after Covid-19 vaccination. Methods: In the period from May to July 2021 we evaluated 33 patients (mean age 54.3±14.1) with “acute vertigo” post Covid-19 vaccination. A detailed medical history was taken on comorbidities, types of vaccines received and symptoms associated. All patients underwent otoneurological evaluation such as HINTS (Head Impulse Test, Nystagmus Evaluation, Test of Skew) Examination. Head Shaking Test induced nystagmus, Hyperventilation induced nystagmus, and parossistic positional nystagmus were studied to search for vestibular impairment. Results: Symptoms included 16 patients (48.5%) with objective vertigo, 14 (42.4%) with subjective vertigo and 3 (9.1%) with dizziness. Of the associated ENT symptoms, the most expressed was tinnitus (18,2%). Bedside examination showed absent nystagmus in 7 patients (21.2%), 9 patients (27.3%) had and horizontal or rotatory nystagmus, 17 patients (51.5%) had a vertical or oblique nystagmus, negative HST or “central HINTS”. Discussion and conclusions: 9 patients had a evoked nystagmus pathognomonic for BPPV; in the remaining 17 cases, peripheral vestibular dysfunction could be excluded and central disorder may be suggested. Due to the prevalence of nystagmus of non-peripheral origin, a central nervous system involvement could be not excluded. However, due to the small sample size, a definite cause-effect relationship between vaccination and vertigo cannot be inferred. In light of expected third dose, large-scale and well-designed studies are needed to better define possible adverse reaction of COVID-19 vaccine.